Prevalence of rubella susceptibility among pregnant mothers in a community-based antenatal clinic in malaysia: A cross-sectional study - Cheong, A.T.; Khoo, Ee Ming (SAGE Publications, 2008)
Introduction: routine rubella antibody screening is not done for antenatal mothers in community health clinics in Malaysia. However, congenital rubella syndrome has persisted with its associated health burden. Objectives: to determine the prevalence of rubella susceptibility among pregnant mothers and its associated risk factors. Methodology: a cross-sectional study was carried out in the Petaling district, Selangor, Malaysia, where 500 pregnant mothers were recruited, and face-to-face interviews were conducted. Rubella IgG tests were performed. Results: the prevalence of rubella susceptibility among pregnant mothers was 11.4. Using logistic regression, a history of not having received rubella vaccination or having unknown rubella vaccination status was found to be a significant predictor for mothers to be rubella susceptible (odds ratio = 2.691; 95 confidence interval = 1.539-4.207). Conclusions: routine rubella IgG screening tests need to be offered to all antenatal mothers in view of the high prevalence found.